2010
DOI: 10.1016/j.cgh.2010.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency of Lynch Syndrome Among Young Patients With Non-Familial Colorectal Cancer

Abstract: BACKGROUND & AIMS-Colorectal cancer (CRC) is uncommon in individuals <50 years old. Lynch Syndrome is caused by germline mutations in DNA mismatch repair (MMR) genes and associated with early-onset CRC, but little is known about the proportion of young patients with apparently sporadic CRC who actually have Lynch Syndrome. We examined patterns of microsatellite instability (MSI) and expression of MMR genes among patients <50 years old with non-familial CRC (patients with more than family member with CRC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 20 publications
11
46
0
Order By: Relevance
“…However, LSs represent 9.2% –21.3% of cases in this subgroup14–21 and this research like other current studies55–57 revealed it is a heterogeneous disease, which includes cases with a high familial component other than LS as well as a substantial proportion of sporadic cases with distal location.…”
Section: Discussionsupporting
confidence: 85%
“…However, LSs represent 9.2% –21.3% of cases in this subgroup14–21 and this research like other current studies55–57 revealed it is a heterogeneous disease, which includes cases with a high familial component other than LS as well as a substantial proportion of sporadic cases with distal location.…”
Section: Discussionsupporting
confidence: 85%
“…There was a strong nuclear reactivity to both hMSH2 and hMSH6 (92.3% to 100%) in all biopsied areas, which is similar to the findings in developed country populations [14,15]. This may be attributed to the fact that since this is a general community hospital, it accepts all types of patients with colorectal carcinoma, thus eliminating selection bias.…”
Section: Discussionsupporting
confidence: 67%
“…Of these 59 patients, most were in the distal colorectum (42/59, 71%), none demonstrated BRAF mutations, and 14/59 (24%) demonstrated KRAS mutations. 24 Our results identified a lower rate of KRAS mutation (4%) in early-onset colorectal carcinoma. The reason for this discrepancy is not entirely clear, although a lower frequency of KRAS mutation was also observed in our control group of carcinomas identified over the age of 40 years.…”
Section: Discussionmentioning
confidence: 48%
“…Goel et al 24 analyzed 75 colorectal carcinomas diagnosed in patients under the age of 50 and identified 59 with proficient mismatch repair. Of these 59 patients, most were in the distal colorectum (42/59, 71%), none demonstrated BRAF mutations, and 14/59 (24%) demonstrated KRAS mutations.…”
Section: Discussionmentioning
confidence: 99%